PENYIMPANGAN SEKSUAL DALAM HUBUNGAN SUAMI ISTRI PERSPEKTIF HUKUM ISLAM DAN UNDANG-UNDANG NOMOR 23 TAHUN 2004 TENTANG KEKERASAN DALAM RUMAH TANGGA (KDRT) - Mawardi, Mawardi (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2017)
This research raises  the problem about  sexual  deviation  in the relationship of husband and wife of Islamic law perspective and Law No. 23 of 2004 on Domestic Violence. Based  on the analysis can be disipmulkan that form of sexual deviation  husband to wife like: (1) sexual  sadism which  is one form of variation in relationship of husband and wife. The behavior  of sexual sadism involves giving a stimulus to her partner in a sadistic way. This behavior  is usually accompanied by the act of tying his partner, close his partner’s  eyes, and silenced his partner’s  mouth. (2) Fucking at the wife’s rectum because it can be likened  to liwath (homo sex), because the rectum is a dangerous and dirty place. Analysis of Islamic law against sexual deviation (sexual sadism) also contains elements of persecution and danger. Which element of persecution and danger  is prohibited by Islam. Because it can harm yourself and others,  and not in accordance with the goals of Islam that brings grace to the universe that requires all human beings to live in a state of serenity and at the same time eliminate the danger  to mankind. While in some verses, the Qur’an has hinted  that Allah Almighty. Do not like people who like to do damage and persecution (kemafsadatan). Sexual lapses  of husbands against wives according to Article 8 Letter A of Law no. 23 of 2004 includes violent acts defined  as any act of coercion of sexual  intercourse, coercion of sexual  intercourse in an unnatural way and or disliked by a wife.